The rs2274911 polymorphism in GPRC6A gene is associated with insulin resistance in normal weight and obese subjects. (21st October 2016) - Di Nisio, Andrea; Rocca, Maria Santa; Fadini, Gian Paolo; De Toni, Luca; Marcuzzo, Giorgio; Marescotti, Maria Cristina; Sanna, Marta; Plebani, Mario; Vettor, Roberto; Avogaro, Angelo; Foresta, Carlo
Summary: Objective: Identification of the novel endocrine role of osteocalcin (OC) and its receptor GPRC6A has given rise to a new branch of research in OC/GPRC6A axis related to glucose metabolism. GPRC6A‐ and OC‐deficient mice share features of the metabolic syndrome, in addition to male infertility. Recently, the polymorphism rs2274911 in GPRC6A was shown to be associated with testicular impairment. We aimed to investigate the role of rs2274911 polymorphism in glucose and lipid metabolism in a cohort of normal weight and obese subjects Design, Patients, Settings: A total of 392 male and females, including 218 obese patients and 174 age‐matched normal weight controls, were retrospectively selected. Results: The distribution of rs2274911 alleles and genotypes did not differ either between normal weight and obese subjects or sexes (all P > 0·05). Age‐ and OC‐adjusted multivariate analysis revealed that, in the normal weight group, fasting insulin and HOMA‐IR increased in GA ( P = 0·016 and P = 0·025) and AA genotypes ( P = 0·033 and P = 0·040) compared with GG homozygotes. In the obese group, AA homozygotes had increased fasting glucose ( P = 0·041 vs GG). Triglycerides, fasting insulin and HOMA‐IR increased in both GA ( P = 0·020, P < 0·001 and P = 0·001) and AA genotype ( P = 0·021, P = 0·013 and P = 0·013). Conclusion: In a cohort of normal weight and obese subjects, we found that the nonrare polymorphism rs2274911 in the GPRC6A gene was associated with insulin resistance features, independently of the metabolic phenotype and OC levels.